How the popularization of dietary guidelines affects healthy eating behavior: Evidence from the choice of staple food structure in China - Shijiu Yin; Huiying Peng; Yuqiu Qin; Zongshuo Yin (Future Foods)
Long-term high consumption of refined grains is detrimental to human health. This study aims to assess the effects of dietary guidelines on healthy eating and provide policy insights for dietary pattern transition. The staple food structure considered in this paper consists primarily of a combination of refined grains (rice and white flour mainly) and whole grains and potatoes in various proportions. Using a nationally representative sample of 102,464 adult respondents drawn from the Food Safety and Nutrition Health Survey (FNS), we discovered that awareness of the Chinese Dietary Guidelines (2016), issued by the Chinese Nutrition Society, can help residents choose a healthier staple food structure by substituting refined grains with a higher proportion of whole grains and potatoes. Further analysis reveals that (a) knowing the dietary guidelines moderates the staple food choices of obese, urban-dwelling, and male groups, effectively improving these groups’ staple food choices; (b) knowing the dietary guidelines also promotes residents’ dietary diversity and vegetable intake; and (c) addressing potential endogeneity due to reverse causality using an instrumental variable approach, our mechanism analysis shows that dietary guidelines primarily promote healthy dietary choices by enhancing nutrition knowledge. This paper examines the health effects of dietary guidelines on residents’ staple food choices and demonstrates the significance of dietary guideline popularization and nutrition knowledge based on dietary guidelines.